Comparison of tobacco-specific nitrosamine levels in smokeless tobacco products: High levels in products from Bangladesh - Nasrin, Shamema (PLoS One, 2020)
Bangladesh exhibits the second highest rate of smokeless tobacco (SLT) product usage in the world, and this has been associated with the high upper aerodigestive tract cancer incidence in this country. The goal of the present study was to examine the levels of the highly carcinogenic tobacco-specific nitrosamines (TSNAs) in Bangladeshi SLT products and compare these levels to that observed in SLT brands from southeast Asia and the USA. The levels of TSNAs and nicotine were determined by LC-MS/MS in twenty-eight SLT brands and several tobacco additives from Bangladesh, as well as several SLT brands from India, Pakistan and the USA. The levels of N-nitrosonornicotine (NNN), 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), N-nitrosoanatabine (NAT) and N-nitrosoanabasine (NAB) in Bangladeshi SLT brands ranged from 1.1–59, 0.15–34, 0.79–45, and 0.037–13 μg/g SLT powder, respectively. The mean levels of the highly carcinogenic TSNAs (NNN+NNK) were 7.4-, 2.4-, and 63-fold higher in Bangladeshi SLT products as compared to SLT brands from the USA, India and Pakistan, respectively; these trends were also observed for NAT and NAB. Similar mean levels of nicotine were observed in the Bangladeshi brands (31 mg/g powder) versus brands from the USA (25 mg/g powder) and India (20 mg/g powder); they were 3-fold higher than brands from Pakistan (10 mg/g powder). Gul SLT brands exhibited the highest pH and the highest levels of unprotonated nicotine. The high levels of TSNAs in Bangladeshi SLT brands may be an important factor contributing to the high rates of upper aerodigestive tract cancer in Bangladesh.